Effect of initial levothyroxine dose on neurodevelopmental and growth outcomes in children with congenital hypothyroidism - Esposito, Andrea; Vigone, Maria Cristina; Polizzi, Miriam; Wasniewska, Malgorzata Gabriela; Cassio, Alessandra; Mussa, Alessandro; Gastaldi, Roberto; Di Mase, Raffaella; Vincenzi, Gaia; Pozzi, Clara; Peroni, Elena; Bravaccio, Carmela; et al. (Frontiers in Endocrinology, 2022)
Objectives: We designed a multicentre open prospective randomized trial to evaluate the risk-benefit profile of two different initial treatment schemes with levothyroxine (L-T4), 10-12.5 μg/kg/day vs 12.6-15 μg/kg/day, on growth and neurodevelopmental outcomes in children with congenital hypothyroidism (CH) detected by neonatal screening to identify the best range dose to achieve optimal neurocognitive development. Design, patients and methods: Children detected by neonatal screening were randomly assigned to receive an initial L-T4 dose of 10-12.5 μg/kg/day (Low) or 12.6-15 μg/kg/day (High). All patients underwent periodical clinical examination with measurement of growth parameters and measurement of TSH and FT4. Neurocognitive development was evaluated at the age of 24 months using Griffiths Mental Development Scales (GMDS) and cognitive and behavioral assessment was performed at 48 months of age using Wechsler Preschool and Primary scale of Intelligence (WIPPSI-III). The study was registered with clinicaltrials.gov (NCT05371262). Results: Treatment schemes below or above 12.5 μg/kg/day were both associated with rapid normalization of TSH and thyroid hormone levels in most patients with no differences in the risk of over- and under-treatment episodes in the first months of life. Growth parameters were normal and comparable between the two groups. Developmental quotients at 24 months of age were normal in both groups (Low 100.6±15.5 vs High 96.9±16.6). Likewise, at 4 years of age IQ and subtest scores were comparable between patients from Low and High (Total IQ 104.2±11.4 vs 101.0±20.3, Verbal IQ 103.9±11.5 vs 98.7±15.1, Performance IQ 105.3±10.4 vs 100.3±19.8). 6/45 CH patients (13.3%) showed a total IQ below 85 (73.7±5.9) regardless of age at diagnosis, L-T4 starting dose, time of FT4 and TSH normalization and episodes of over and undertreatment. Worse socioeconomic status and delayed bone age at diagnosis were the only predictors of an increased risk of having suboptimal IQ at 24 and IQ at 48 months. Conclusions: Our results indicate that initial treatment with L-T4, 10-12.5 μg/kg/day vs 12.6-15 μg/kg/day, are both associated with normal growth and neurodevelopmental outcomes in children with CH detected by neonatal screening. Further studies with a long-term follow-up on a larger number of patients are needed to confirm these results.